Math, asked by Anonymous, 5 months ago

solve :-
[ \:  \frac{ {6}^{2}( {6}^{7} -  {6}^{8} )  }{ {6}^{6} } ]

Answers

Answered by prince5132
18

GIVEN :-

  • 6²(6⁷ - 6⁸)/6².

TO FIND :-

  • The value of 6²(6⁷ - 6⁸)/6².

SOLUTION :-

 \implies \sf \:  \dfrac{6 ^{2}  \bigg(6 ^{7}  - 6 ^{8} \bigg) }{6 ^{6} }  \\

\implies \sf \:  \dfrac{6 ^{2} \times 6 ^{7}  - 6 ^{2}  \times 6 ^{8}  }{6 ^{6} }  \\

\implies \sf \: \dfrac{6 ^{2 + 7}  - 6 ^{2 + 8} }{6 ^{6} }  \\

\implies \sf \: \dfrac{6 ^{9}  - 6 ^{10} }{6 ^{6} }  \\

\implies \sf \: \dfrac{6 ^{9} }{6 ^{6} }  -  \dfrac{6 ^{10} }{6 ^{6} }  \\

\implies \sf \:6 ^{3} - 6 ^{4}   \\

\implies \sf \:216 - 1296 \\

\implies  \underline{ \boxed{\sf \:\dfrac{6 ^{2}  \bigg(6 ^{7}  - 6 ^{8} \bigg) }{6 ^{6} } =  - 1080}}

Answered by Anonymous
2

[6²(6³*6⁴ - 6⁴*6⁴)] / 6⁶

[6²{6⁴(6³ - 6⁴)}] / 6⁶

[6²*6⁴(6³ - 6⁴)] / 6⁶

[6⁶(6³ - 6⁴)] / 6⁶

6³ - 6⁴

216 - 1296

-1080

Similar questions